Model of Giving Jamu Bejja and Oxytocin Massage in Improving Production of Breast Milk and Uterine Involution - Suryaningsih Suryaningsih; Feftin Hendriyani (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Breast milk is the best food for babies. WHO set an exclusive breastfeeding target of at least 50%, but the coverage of exclusive breastfeeding in Indonesia still reaches 32% to 38%. Similarly, in East Java, especially Bangkalan, exclusive breast milk coverage is still at 29.1%. The production of breast milk is influenced by various factors, namely breastfeeding education, early breastfeeding initiation, breastfeeding techniques, stress, and nutrients consumed. There has been no research on oxytocin massage and Jammu Bejja on the production of breast milk or uterine involution. Therefore, there need to be efforts to increase the production of breast milk by giving back massage combined with consuming supplement intake by drinking Jamu Bejja Madura. Methods used observational analytics with a cross-sectional approach, to obtain modeling, followed by the preparation of modules previously conducted field surveys and expert consultation. The population consisted of postpartum mothers in Arosbaya, Klampis, Blega. Samples were taken as many as 130 postpartum mothers. Variables were oxytocin massage, herbal medicine, breast milk production, and uterine involution. Data collection using questionnaires and analyzed using Partial Least Square. The results showed that oxytocin massage and herbal medicine had an effect of 84.3% on the production of breast milk and 83.7% on uterine involution. It can be concluded that oxytocin massage affects the production of breast milk and uterine involution, Jammu bejja affects uteri involution. It is expected that postpartum mothers get the services of oxytocin massage and herbal medicine to increase the production of breast milk and involution uteri. Keywords: model; Jammu Bejja; oxytocin massage; breast milk production